Cartografia do close: platôs de festivos, platôs musicais - Lacava, Vyullheney Fernandes de Araújo (2016)
Our research program runs through the musicality circuit in Galpão29, which is located in the neighborhood of Ribeira, in Natal-RN. From this location we seek to draw a cartography of musicality spaces. In Natal’s night opened up spaces for action of collective organizers of parties, inviting young people to attend the events present at the festive agenda of Galpão29. The festivities opened environments, and in their midst, invited the participants to the action. The notion of close, in our thesis, seeks to present the form of relationship between bodies with the environments present in our city. On those parties we could find young people pouring their desires in their own bodies, microphones, announced flyers of events, calls for consideration and participation of performances. We found DJs and bands who composed musical productions and spread it in the costumes, to act on stage. The public were faced with participants acting in the scene by creating their own closes. We questioned the creation of work spaces where momentary freedoms are realized, where the body drunk to music and moves of everyday overcodings of city’s life. The creation of festive plateaus make up micropolitical effects on the city’s scene, through the celebration of life and composition of musicality that are expressed in their minor effects. Then we draw a cartography of close, showing how the creation of spaces and performances take place in Natal’s scene between the flashes captured in the events and how the closes are dragged to other city environments.